Early exposing preclinical undergraduate medical students to communication-skills: a pre-test post-test experimental study - Timilsina, Sameer; Karki, Sirisa; Mishra, Roshan; Shrestha, Barun; Deo, Gopendra Prasad (Journal of Chitwan Medical College, 2021)
Background: Effective physician-patient communication is integral to building confidence, improving patient compliance, satisfaction, and, avoiding mishaps, and, malpractice suits. Communication-skills (CS) training is an internationally accepted essential component of medical education. This study aims to assess the communication-skills knowledge of pre-clinical undergraduate medical students pre- and post- CS course. We expect an improvement in CS knowledge post-intervention. Methods: Between March and September 2019, 100 first year pre-clinical undergraduate medical students at Chitwan Medical College were enrolled in CS course. The intervention was conducted in 10 team-based learning (TBL) sessions on selective study areas based on Calgary-Cambridge model. Attitude towards learning CS using communication skills attitude scale (CSAS) and assessment on knowledge of CS was conducted pre- and post-intervention. Results: Among 100 students, 70% were males and 30% females. Positive attitude towards learning CS improved by 5%. Statistically significant progress was noted in post-intervention mean scores implying CS to be teachable and learnable. (Wilcoxon Signed ranks test z=-6.178 p<0.001). Knowledge on medical CS improved in the study participants irrespective of sex, entry-type, past-educational institute or attitude. Students with pre-intervention negative attitude showed marked improvement in post-intervention knowledge score (z=-5.674 p<0.001). Conclusions: The intervention was effective in increasing students’ knowledge of medical CS, but we did not assess the skills of the students. Continuation of this study is recommended to explore whether CS training could actually improve soft skills of medical students in our part of the world.